2021
DOI: 10.3390/agronomy11050976
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Conjugate Complexes of Chitosan and Urtica dioica or Equisetum arvense Extracts for the Control of Grapevine Trunk Pathogens

Abstract: In the work presented herein, we analyze the efficacy of three basic substances that comply with European Regulation (EC) No 1107/2009, namely chitosan, horsetail (Equisetum arvense L.) and nettle (Urtica dioica L.), for the control of grapevine trunk diseases (GTDs) in organic farming. The E. arvense and U. dioica aqueous extracts, prepared according to SANCO/12386/2013 and SANTE/11809/2016, have been studied by gas chromatography–mass spectrometry (GC-MS), identifying their main active constituents. The thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…The bioactive constituents present in each of the extracts, characterized by gas chromatography-mass spectroscopy (GC-MS), have been reported in previous works [19][20][21].…”
Section: Preparation Of Plant Extractsmentioning
confidence: 97%
See 2 more Smart Citations
“…The bioactive constituents present in each of the extracts, characterized by gas chromatography-mass spectroscopy (GC-MS), have been reported in previous works [19][20][21].…”
Section: Preparation Of Plant Extractsmentioning
confidence: 97%
“…After cooling, the decoction was filtered and diluted by a factor of 10 with water to obtain a final concentration of 2 mg•mL −1 . For the nettle extract, dried nettle leaves (15 g•L −1 ) were macerated for 3-4 days at 20 • C, followed by filtering and dilution of the filtrate to obtain a final concentration of 2 mg•mL −1 [19].…”
Section: Preparation Of Plant Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, none of the aforementioned combinations are conjugated complexes, and the existence of interactions between the two components in terms of antimicrobial activity was not explored. Albeit for other phytochemicals different from the ones present in L. binervosum, a synergistic behavior upon conjugation with COS was reported in the literature against phytopathogens: e.g., for horsetail (Equisetum arvense L.) and nettle (Urtica dioica L.) extracts against eight fungal species involved in grapevine trunk diseases [68], with EC 90 values in the 208-1000 µg•mL −1 range (depending on the extract and on the Botryosphaeriaceae taxa). The value reported in this work for the COS-flower extract complex (914 µg•mL −1 ) would be on the upper limit.…”
Section: On the Synergistic Behavior Observed For The Conjugate Complexesmentioning
confidence: 98%
“…They point out the relationship of pathogen density and effectiveness of the basic substance to hamper the pathogen. Langa-Lomba et al (2021) found synergistic effects, while using chitosan-polymers in combination with an E. arvenseextract. For a phytosanitary programme, these approaches, the combination of copper or chitosan with E. arvenseextract can compensate for the expected lack of efficiency between a basic substance and a conventional or chemical plant protection product.…”
Section: Discussionmentioning
confidence: 95%